Evolving Criteria for Identification and Selection of Core Periodicals in a Subject: A Case Study on Indian Horticulture - Asundi, A. Y.; Humayoon Kabir, S. (Journal of Information and Knowledge, 1996)
The paper presents a new criteria evolved by experience to identify a list of core and selected Indian periodicals in Horticulture. A study of citations from the doctoral and master’s degree dissertations in the field of Horticulture from 1980 to 1989 as the main source of data is computed for this study. A list of 235 primary periodicals and a ranking list has been prepared out of this study. The criteria used for selecting core journals in most of the studies are by ranking only, and has certain limitations. In this study 35% of the citations are on the subject journals (i.e., 16% of the total). Since this limits to a very small percentage, identification of other criteria was found necessary such as identifying subject coverage in peripheral subjects like in Agricultural Sciences, Science and so on. This process generated 95% of the citations from 85% of the journals. Such additional criteria are identified in the study and rank journals for the selection of core items.